The Impact of Firm-Provided Training on Production: Testing for Firm-Size Effects - Jan M.P. de Kok (Tinbergen Institute, 2000)
The returns to firm-provided training depend on many differentfactors. Firm size is an importantindicator of various of these factors, but recent research tends toneglect it. In this study thereturns to firm-provided training are estimated, taking account ofthree possible firm-sizeeffects: the HRM effect, selection effect and scale effect. Usingpanel data on 173 Dutch firms,support is found for the existence of the HRM effect: trainingsupport per working day (theaverage time a firm spends on setting up and coordinating a trainingprogram) has a positiveinfluence on the returns to training. In the absence of trainingsupport, training has no effect onproduction. Since on average smaller firms provide less trainingsupport per working day, thisimplies that small firms benefit less from firm-provided trainingthan their larger counterparts.
Keywords: 330; Betriebliches Bildungsmanagement; Niederlande